An ultrahigh-strength steel produced by heavy warm rolling of the metastable austenite. (December 2019) - Zheng, Han; Fu, Liming; Li, Ziyong; Ji, Xinbo; Wang, Qijiang; Wang, Wei; Shan, Aidang
Graphical abstract: Highlights: Ultrahigh-strength high-ductility steel is fabricated by heavy warm rolling and tempering. Ultrafine-grained martensite is transformed from deformed ultrafine metastable austenite. Grain refinement and dislocation hardening are main strengthening mechanisms. Abstract: An ultrahigh-strength steel with sufficient uniform elongation (UE) and high strain-hardening ability was fabricated by a combination method of heavy warm rolling (HWR) on the metastable austenite and subsequent quenching (Q). The WR-Qed steel shows an ultra-fine martensitic structure with an average effective grain size (EGS) of 0.57 μm, yield strength (YS) of 1911 MPa and ultimate tensile strength (UTS) of 2411 MPa. The tempering (T) effect on microstructure and properties of the steel was investigated. Compared with the heavily hot-rolled and tempered steel, the WR-QTed steels exhibited substantial enhancement in strength, ductility and strain-hardening ability. After tempering at 200 ℃ for 1 h, the WRed steel demonstrated an excellent strength-ductility combination with a YS of 1905 MPa, UTS of 2163 MPa and total elongation of 11.7%. Grain refinement and dislocation strengthening play major roles in enhancing strength. It is believed that the heavy warm deformation can effectively refine the metastable austenite grains and consequently result in the ultrafine-structured steel by martensitic transformation during the subsequent quenching. The excellent strength-ductility combinations of the WR-Qed steel are also closely associated with effect of ultrafine lamellar structures of martensite, nano-twins and high density low-angle grain boundaries.